Analysis of the Role of Epidemiology in Community-Based Infectious Disease Control - Putri, Shalsabilla Novelita; Alia Asy-Syifa (PT Yapindo Jaya Abadi, 2025)
ABSTRACT This study aims to analyze the role of epidemiology in controlling infectious diseases through a community-based approach, emphasizing its contribution to strengthening public health resilience and participatory prevention systems. Using a qualitative descriptive method through a literature study, data were obtained from peer-reviewed journal articles, official reports, and academic publications published between 2015 and 2025. Data were analyzed inductively through thematic identification, data reduction, conceptual categorization, and synthesis. The findings show that integrating epidemiological frameworks with community participation enhances disease surveillance, early detection, behavioral change, and health education. Community-based strategies such as participatory surveillance, capacity building for health workers, and digital innovations like mobile health and wastewater-based epidemiology have proven effective in improving responsiveness and sustainability. The study expands the theoretical scope of epidemiology from a purely biomedical discipline to a socio-epidemiological paradigm that values cultural and behavioral contexts. Practically, it highlights the importance of empowering communities as co-creators of health data and solutions. Despite the limitation of relying on secondary data, this research provides a comprehensive understanding of how participatory epidemiology can strengthen equitable, inclusive, and adaptive health systems. Future research should combine mixed methods and field-based approaches to deepen contextual insights and enhance practical application. Keywords: epidemiology, community-based approach, infectious disease control, participatory surveillance, public health.